2013
DOI: 10.1177/0954406213512120
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic peculiarities of alpha-type Stirling engines for low-temperature difference power generation: Optimisation of operating parameters and heat exchangers using a third-order model

Abstract: Low-temperature heat sources such as waste heat and geothermal energy in the range from 100 ℃ to 200 ℃ are widely available and their potential is largely untapped. Stirling engines are one possibility to convert this heat to a usable power output. Much work has been done to optimise Stirling engines for high-temperature heat sources such as external combustion or concentrated solar energy but only little is known about suitable engine layouts at lower temperature differences. With the reduced temperature diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…The indicated power generated at a phase angle of 90° is 714 W, which is 5% lower than that at 105°. This deviation could be more pronounced at higher engine frequencies [27].…”
Section: Compression Expansionmentioning
confidence: 91%
“…The indicated power generated at a phase angle of 90° is 714 W, which is 5% lower than that at 105°. This deviation could be more pronounced at higher engine frequencies [27].…”
Section: Compression Expansionmentioning
confidence: 91%
“…Hoegel et al [4] performed a theoretical analysis of the operating and geometric parameters of low-temperature difference Stirling engines. The engine was an alpha type using helium at a mean pressure of 5 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pressure difference can be reduced by increasing the phase angle and dead volume. In addition, increasing the phase angle leads to an increase in the heat transfer, and thus the conventional choice of the 90 o phase angle is mainly due to mechanical design reasons …”
Section: Introductionmentioning
confidence: 99%
“…In fact, many researchers showed that it is important to tune the phase angle to achieve the optimal performance of a Stirling engine. Høeg et al showed that the Franchot engine in the SPP 4‐106 heat pump is chosen for the ability to use phase angles other than 90°, especially with low temperature sources.…”
Section: Introductionmentioning
confidence: 99%